Development of participatory Buddhist tourism routes In the area of Phra That Yaku, Kamalasai District, Kalasin Province - Sudassanavibhãnĩ, Phramaha Natthabhan; kittimatee, Phramaha kitti; PhraMedhiwatcharajarn,; Kitjasaro, Phramaha Michai; Sutheero , Phramaha Pongtaratid (Journal of Modern Learning Development, 2024)
he research study on “Development of Participatory Buddhist Tourism Routes in Phra That Yaku, Kamalasai District, Kalasin Province” aimed to 1) study the history and value of Buddhism in Phra That Yaku, Kamalasai District, Kalasin Province, 2) survey the status of participatory Buddhist tourism in the Buddhist dimension in Phra That Yaku, Kamalasai District, Kalasin Province, and 3) to upgrade Buddhist tourism in Phra That Yaku, Kamalasai District, Kalasin Province. This research was a mixed method research, quantitative research, calculating the appropriate sample size for the research using Taro Yamane’s formula at 400 monks/person, and qualitative research, in-depth interviews using an interview form to collect data in the target group of 12 monks/person, which was a survey research and in-depth interviews with key informants. The researcher was able to analyze the results of the data analysis. The research results found that 1. History on the dimensions of people, time, place and analysis of the value in the dimension of Buddhism in the area of ​​Phra That Yaku, Kamalasai District, Kalasin Province found that Kalasin Province is a country with cultural and religious diversity. Neutrality and flexibility in accepting and adapting to other cultures make tourism diverse and interesting from the online world in contrast to the offline world because it is actually created by human hands. Tourist attractions are very important because they are beautiful in architecture and have historical and religious significance. Culture and art Tourism provides good opportunities to experience local culture. Visiting performances of arts and crafts created by villagers Participating in activities related to local culture such as national festivals, religious festivals and local festivals Supporting community tourism helps promote local development and generate income for communities in various areas, which distributes income and promotes the prosperity of tourism communities that are responsible for the environment. 2. The process of participation in the Buddhist dimension in the area of ​​Phra That Yaku, Kamalasai District, Kalasin Province found that 173 males, accounting for 56.8 percent, most of the people were between 36 and 45 years old, 144 people, accounting for 36.9 percent, were married, 198 people, accounting for 49.5 percent, most of them had bachelor's degrees, 153 people, accounting for 38.3 percent, and were merchants, 196 people. The overall was at a high level, the overall was at a high level ( = 3.98). The overall integration of tourism behavior was at a high level ( = 3.87). People of different genders, different ages, different education, different marital status, different occupations, and different monthly incomes affected the development of participatory Buddhist tourism routes in the area of ​​Phra That Yaku, Kamalasai District, Kalasin Province. The overall was different. Therefore, the hypothesis is accepted. People have different social structure behaviors, different educational institutions, different political behaviors, religious behaviors/arts/traditional cultures, and the development of participatory Buddhist tourism routes. In the area of ​​Phra That Yaku, Kamalasai District, Kalasin Province, by integrating tourism behavior, the overall picture is different, so the hypothesis is accepted. 3. Buddhist tourism routes in Phra That Yaku area, Kamalasai District, Kalasin Province, by community participation, found that organizing exhibitions related to important Buddhist days, organizing activities on important days of the monarchy, such as making merit by offering alms, preaching sermons, organizing meditation, candlelight processions, organizing exhibitions related to royal duties, organizing activities on important days according to traditions/localities, such as making merit by offering alms, preaching sermons, practicing meditation, activities promoting culture/traditions, organizing exhibitions to disseminate knowledge related to important days of traditions/target localities.